1987
DOI: 10.1016/0266-7681(87)90053-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound in the diagnosis of scaphoid fractures

Abstract: A prospective study of the possibility of confirming clinically suspected scaphoid fractures was carried out over one year. Analysis of the results suggest that ultrasound scanning of suspect scaphoid fractures is a reliable method of assessing this condition. It has one weakness in that the diagnosis is based on subjective sensation and this may at times be faulty. Our results, however, suggest that once practice in the technique has been achieved, then mistakes are rarely made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Therapeutic wavelengths often, but not consistently, elicit pain at the fracture site. [4][5][6] There were no reports of pain or discomfort while using the 10 MHz probe over the fracture site.…”
Section: Discussionmentioning
confidence: 96%
“…Therapeutic wavelengths often, but not consistently, elicit pain at the fracture site. [4][5][6] There were no reports of pain or discomfort while using the 10 MHz probe over the fracture site.…”
Section: Discussionmentioning
confidence: 96%
“…Fifteen studies published between 1982 and 2009 assessed the diagnostic accuracy for various physical examination tests, either in isolation or in combinations, including signs such as swelling or discoloration, as well as symptoms like anatomical snuffbox tenderness, scaphoid tubercle tenderness, clamp sign, resisted pronation or supination, thumb compression-induced pain, and US pain. 5,14,[17][18][19][21][22][23]39,[41][42][43][44][45][46] None were from the United States, and 12 were from Europe. These were all prospective case series, and 11 were ED-based, while two were orthopedic clinic studies and two did not report their clinical settings.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…A "positive" US is defined as pain produced when US imaging commences. [18][19][20][21][22][23] Other physical examination maneuvers include assessment of pain in the scaphoid with ulnar or radial deviation of the wrist or with resisted supination (Data Supplement S6, available as supporting information in the online version of this paper) and pronation. 24 Two diagnostic meta-analyses have been published in the orthopedic surgery literature to evaluate advanced imaging modalities for scaphoid fracture, but none focus on history and physical examination diagnostic accuracy or ED-specific pretest probability, all necessary to facilitate Bayesian reasoning for bedside clinicians.…”
mentioning
confidence: 99%
“…Though its mode of action is unclear, ultrasonic energy in the therapeutic range is known to be capable of producing pain or severe tingling when applied to fractures less than 2 weeks old (Nitz & Scoville, 1980;Bedford et al, 1982;Shenouda & England, 1987). In the latter two studies, a strong but not absolute correlation was found between the presence of a recent scaphoid fracture and pain.…”
Section: Introductionmentioning
confidence: 97%